Longitudinal TNFR1 and TNFR2 and Kidney Outcomes: Results from AASK and VA NEPHRON-D. Issue 5 (May 2022) - Chen, Teresa K.; Coca, Steven G.; Estrella, Michelle M.; Appel, Lawrence J.; Coresh, Josef; Thiessen Philbrook, Heather; Obeid, Wassim; Fried, Linda F.; Heerspink, Hiddo J.L.; Ix, Joachim H.; Shlipak, Michael G.; Kimmel, Paul L.; et al.
Significance Statement: Recent research suggests that biomarkers of the TNF pathway (TNFR1 and TNFR2) are associated with worse kidney outcomes. Most of these studies, however, evaluated baseline levels rather than longitudinal changes. In two cohorts (AASK, which enrolled Black people with CKD attributed to hypertension, and VA NEPHRON-D, which enrolled veterans with albuminuric CKD and type 2 diabetes), greater longitudinal increases in serum or plasma TNFR1 and TNFR2 were associated with higher risks of ESKD in AASK and subsequent kidney function decline in VA NEPHRON-D. These associations were independent of baseline biomarker level and kidney function. Longitudinal trajectories in TNFR1 and TNFR2 may ultimately allow improved risk assessment for kidney failure in persons with CKD. Abstract : Background: Higher baseline levels of soluble TNF receptors (TNFR1 and TNFR2) have been associated with progressive CKD. Whether longitudinal changes in these biomarkers of inflammation are also associated with worse kidney outcomes has been less studied. Methods: We evaluated associations of longitudinal changes in TNFR1 and TNFR2 with ESKD in the African American Study of Kidney Disease and Hypertension (AASK; 38% female; 0% diabetes) and kidney function decline (first occurrence of ≥30 ml/min per 1.73 m 2 or ≥50% eGFR decline if randomization eGFR ≥60 or <60 ml/min per 1.73 m 2, respectively; ESKD) in the Veterans Affairs Nephropathy in Diabetes trial (VA NEPHRON-D; 99% male; 100% diabetes) using Cox models. Biomarkers were measured from samples collected at 0-, 12-, and 24-month visits for AASK (serum) and 0- and 12-month visits for VA NEPHRON-D (plasma). Biomarker slopes (AASK) were estimated using linear mixed-effects models. Covariates included sociodemographic/clinical factors, baseline biomarker level, and kidney function. Results: There were 129 ESKD events over a median of 7.0 years in AASK ( n =418) and 118 kidney function decline events over a median of 1.5 years in VA NEPHRON-D ( n =754). In AASK, each 1 SD increase in TNFR1 and TNFR2 slope was associated with 2.98- and 1.87-fold higher risks of ESKD, respectively. In VA NEPHRON-D, each 1 SD increase in TNFR1 and TNFR2 was associated with 3.20- and 1.43-fold higher risks of kidney function decline, respectively. Conclusions: Among individuals with and without diabetes, longitudinal increases in TNFR1 and TNFR2 were each associated with progressive CKD, independent of initial biomarker level and kidney function.